COPD in patients after heart transplantation is associated with a prolonged hospital stay, early posttransplant atrial fibrillation, and impaired posttransplant survival - Rivinius, Rasmus; Helmschrott, Matthias; Ruhparwar, Arjang; Schmack, Bastian; Darche, Fabrice Fernand; Thomas, Dierk; Bruckner, Thomas; Katus, Hugo; Ehlermann, Philipp; Dösch, Andreas (Clinical epidemiology, 2018)
Objectives: COPD is associated with reduced physical activity, an increased risk for pulmonary infections, and impaired survival in nontransplant patients. The aim of this study was to investigate the influence of COPD in patients after heart transplantation (HTX). Methods: We performed an observational retrospective single-center study of 259 patients receiving HTX at Heidelberg University Hospital between 2003 and 2012. Patients were stratified by the Tiffeneau index (forced expiratory volume in 1 second/forced vital capacity [FEV1/FVC]) <0.70 before HTX. The analysis included demographics, posttransplant medication, length of the initial hospital stay after HTX, early posttransplant atrial fibrillation (AF), mortality, and causes of death. Results: In total, 63 (24.3%) patients had an FEV1/FVC <0.70. These patients showed a prolonged hospital stay after HTX (52.0 days vs 43.4 days, mean difference (MD) = 8.6 days, 95% CI: 0.2, 17.0 days), a higher rate of early posttransplant AF (19.0% vs 8.2%, MD = 10.8%, 95% CI: 0.4%, 21.2%), and an increased 30-day mortality (9.5% vs 2.6%, HR = 3.79, 95% CI: 1.16, 12.40). Kaplan-Meier analysis showed a significant inferior 5-year survival in patients with an FEV1/FVC <0.70, along with a higher percentage of death due to transplant failure and infection/sepsis. In addition, a multivariate analysis for mortality within 5 years after HTX indicated an FEV1/FVC <0.70 as a significant risk factor for impaired 5-year posttransplant survival (HR =4.77, 95% CI: 2.76, 8.22). Conclusion: COPD in patients after HTX is associated with a prolonged hospital stay, early posttransplant AF, and impaired posttransplant survival. Keywords: atrial fibrillation, COPD, heart transplantation, mortality, spirometry, Tiffeneau index